Fibro Epithelial Polyp at Unusual Site a Rare Presentation. a Case Report - Dr. Usha Kataria (International Journal of Allied Medical Sciences and Clinical Research, 2020)
A 16 year old male patient presented with group of papular skin lesions over the postero-lateral side of right thigh for last two years, lesions were gradually increasing in size. There was no family history of such lesions. Skin biopsy was taken and sent for histo-pathological examination. The case was diagnosed as of fibro epithelial Polyp and there were no malignant changes.